Sobre uma suposta teoria do erro no alvorecer da filosofia de Nietzsche - Temp, Daniel (2021)
The assertion that knowledge is through and through anthropomorphic is part of a varied repertoire of ideas, sentences and statements that express more or less uniformly one of the most unusual aspects of Nietzsche's meditation on knowledge, notably, the clearly paradoxical idea that knowledge carries something illusory, that the theoretical discourse does not capture or even falsify reality, that truth is nothing but an error. Since, on the one hand, such an idea derives from an earlier reflection that unfolds according to a sinuous argumentative logic and that in addition has its particular assumptions; and since, on the other hand, as supposed knowledge, neither this reflection nor its assumptions escape the drastic denial contained in the very idea that knowledge is error, it is claimed in the present study that Nietzsche's reflection on the erroneous character of knowledge can be freely understood as a theory: only instead of a theory of knowledge, it is maintained that it must rather to be understood as an error theory. Concretely, it is claimed, first, that Nietzsche's reflections trace an aporia in the very concept of knowledge; and, later, that this aporia invariably affects the self-portrait of beings who understand themselves as knowing beings. In this sense, despite the aporetic idea that knowledge is erroneous, the error theory attributed to the philosopher is less a drastic variant of skepticism, and more a theory concerned with showing that the discovery of such an aporia is inevitable for someone who thinks knowledge as we traditionally think.